Pharmacokinetic data on brivaracetam, lacosamide and perampanel during pregnancy and lactation. Issue 2 (15th June 2021) - Landmark, Cecilie Johannessen; Rektorli, Lene; Burns, Margrete Larsen; Revdal, Eline; Johannessen, Svein I.; Brodtkorb, Eylert
Abstract: We present pharmacokinetic data during pregnancy and lactation for brivaracetam, lacosamide and perampanel based on two case studies. Patient 1 used brivaracetam as monotherapy and gave birth to twins. Patient 2 used a combination of brivaracetam, lacosamide and perampanel. In both patients, serum drug concentrations were monitored throughout the pregnancies. Drug concentrations were also analysed in umbilical cord blood at birth, in serum from the offspring and in breastmilk after five days and 3–11 weeks. There were minor changes in concentration/dose‐ratios for brivaracetam and lacosamide. The mean milk/serum ratios for brivaracetam and lacosamide were 0.71 and 0.83, respectively, five days and 3–5 weeks after delivery. The perampanel serum concentration increased by up to 80% in Patient 2 during the last part of gestation. The mean milk/serum‐ratio for perampanel was 0.13, unchanged from five days to five weeks after delivery. Whereas serum concentrations of brivaracetam and lacosamide remained fairly stable throughout pregnancy, perampanel concentrations seemed to steadily increase towards the end. The distribution to milk was considerable for brivaracetam and lacosamide and low for perampanel. More studies on mother‐infant pairs are warranted to confirm these results in larger groups.